Coparenting after marital dissolution and children's mental health: a systematic review, - Diogo Lamela; Bárbara Figueiredo (Elsevier, 2016)
Abstract Objective: Research has shown that coparenting is a vital family mechanism in predicting mental health in children and adolescents. Considering the increasing prevalence of marital dissolution in Western societies, the objective of this systematic review was to summarize the key results of empirical studies that tested the association between mental health of children and coparenting after marital dissolution. Data source: The studies were obtained from three databases (PsycInfo, PubMed, and Web of Knowledge), published between January 2000 and October 2014. The titles, abstracts, and key words of the generated citations were independently reviewed by two investigators to consensually select the articles that met the inclusion criteria. Articles that used psychometrically valid tools to measure at least one mental health indicator and at least one dimension of coparenting in samples with divorced parents were included in the review. Data synthesis: Of the 933 screened articles, 11 met the inclusion criteria. Significant positive associations were found between coparental conflict and behavioral problems and symptoms of anxiety, depression, and somatization. Significant positive associations were also found between other specific dimensions of coparenting (coparental support, cooperation, and agreement), overall mental health, self-esteem, and academic performance. Conclusions: The integrated analysis of these studies suggests that coparenting is a key mechanism within the family system for the prediction of child mental health after marital dissolution, and thus, it is recommended that pediatricians, psychologists, and other health professionals consider coparenting as a psychosocial variable for children's mental health assessment and diagnosis.